Capital Market Efficiency and Arbitrage Efficacy. (10th June 2016) - Akbas, Ferhat; Armstrong, Will J.; Sorescu, Sorin; Subrahmanyam, Avanidhar
Abstract: Efficiency in the capital markets requires that capital flows are sufficient to arbitrage anomalies away. We examine the relation between flows to a quantitative (quant) strategy that is based on capital market anomalies and the subsequent performance of this strategy. When these flows are high, quant funds are able to implement arbitrage strategies more effectively, which in turn leads to lower profitability of market anomalies in the future, and vice versa. Thus, the degree of cross-sectional equity market efficiency varies across time with the availability of arbitrage capital.